The legal nature of the exceptio veritatis criminal libel (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
While the exceptio veritatis (defence of the truth) clause enjoys a long tradition in Spanish Criminal Law as a defence against prosecution for criminal libel (calumny), there is an on going debate among the scholars over its legal nature. This paper studiesthe role of the exceptio veritatis clause: some general considerations are followed by a conceptual examination of the criminal offence of libel and a concise review of its inclusion in successive Spanish Criminal Codes enacted from 1822 on. Finally, the paper describes the main positions on the legal nature of this clause.
Keywords: Libel (calumny); exceptio veritatis (defence of justification; defence of truth); legal nature; element of a criminal offence